Визуальное vs. вербальное художественное пространство в семиотике Юрия Михайловича Лотмана. Исследование натюрморта - Naiditch, Larissa (Studia Rossica Posnaniensia, 2025)
The article examines the ideas of Juri Mikhailovich Lotman about the triple opposition: a thing, its image and its designation by word, and develops Lotman’s ideas on the semiotics of still life. The parallels between a pictorial still life and a verbal utterance are shown in the article using several examples (still lives of different time periods – from the Hermitage painting by Jan Davidsz de Heem to the lithographs of Elena Galerkina; poems by Alexander Pushkin, Sasha Chorny, Joseph Brodsky). The objects depicted in the still life seem to imply constancy, reflecting a frozen, unchanging life. This corresponds to beingness, which is conveyed at the verbal level by nominative syntactic constructions. However, the static nature of the image, as well as the elements of the text, does not exclude the emergence of a hidden narrative, inherent in both pictorial and verbal utterance. The time axis and the “implicit verbality” associated with it are especially important here. The emergence of a plot in a still life can be obvious or “optional”, based only on the imagination and associations of the viewer. Discovering the “coherence of the text” and the emergence of a narrative, we come across one interesting feature. The “story” takes place where people, not depicted but assumed, seem latently to appear in the still life. The relationship between the depicted objects is considered against the background of the linguistic category of text coherence, which is reflected in semantic and grammatical agreement.